2018
DOI: 10.3390/app8122585
|View full text |Cite
|
Sign up to set email alerts
|

A Measurement System for Time Constant of Thermocouple Sensor Based on High Temperature Furnace

Abstract: In dynamic temperature measurement, thermocouple sensors are widely used, and their dynamic characteristics directly affect the accuracy of the test results. So before applying thermocouple sensors to dynamic temperature measurement, their dynamic characteristics should be obtained, and their dynamic performance parameters should be analyzed. The time constant is the most important dynamic parameter, which reflects the response speed of a thermocouple sensor. Therefore, it is necessary to measure the time cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…However, step functions of temperature and humidity are not possible in real-world conditions. Instead, Li et al (2018) used a ramp function to model the thermodynamic shock and found that the error of assuming an ideal step function is less than 10% if the transition time from the initial to the final state is less than the time response of the sensor. According to the iMet-XF bead thermistor datasheet, the sensor response time can be less than 1sec.…”
Section: Forward Model Of Humidity Sensormentioning
confidence: 99%
“…However, step functions of temperature and humidity are not possible in real-world conditions. Instead, Li et al (2018) used a ramp function to model the thermodynamic shock and found that the error of assuming an ideal step function is less than 10% if the transition time from the initial to the final state is less than the time response of the sensor. According to the iMet-XF bead thermistor datasheet, the sensor response time can be less than 1sec.…”
Section: Forward Model Of Humidity Sensormentioning
confidence: 99%
“…However, under normal operational conditions, the sensor will be responding to temperature changes in the surrounding medium. Creating well-known and reproducible dynamic temperature changes in the medium is challenging to perform experimentally: the plunge method may be used to produce a temperature step [ 17 , 18 , 35 , 36 , 50 ], and a ramp input may be produced by rapid insertion into an oven [ 37 , 68 , 70 ]; however, there are limitations to these methods as described in Section 1 . Therefore, a FE transient heat-transfer model was used to study the sensors’ response to changes in the temperature of the surrounding medium, and the experimental results described above were used to validate the model.…”
Section: Dynamic Characterisation: Computational Modellingmentioning
confidence: 99%
“…Characterising the dynamic response can be challenging: a common method is to rapidly immerse the sensor into water at a different temperature to the ambient room temperature, providing temperature step input [ 17 , 18 , 35 , 36 , 50 ]. However, limitations to this technique include errors caused by unknown temperature gradients in the air and water, uncontrolled speed and depth of immersion [ 68 ], and temperature gradients in the fibre that would not be present in normal use. The speed of response is also strongly dependent on the thermal properties of the medium surrounding the sensor, and it is challenging to study this dependence using the immersion method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the sintering process is required for fabricating the THA tubular part, controlling the sintering temperature is very important. Accurate measurement and control of temperature during high-temperature processes are important because it affects the product quality and operational performance [35][36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%